Necrotic acalculous cholecystitis in an 8-year-old boy: a case report - Fanny Mueller; Amy McDonald; Vera S. Schellerer (Journal of Medical Case Reports)
Abstract Background Although its incidence has increased in recent years, gallbladder inflammation in childhood is generally a rare condition. Acute acalculous cholecystitis accounts for about 50–70% of gallbladder inflammation in childhood, mostly in previously healthy children. The onset is strongly associated with viral, bacterial, or parasitic infections. Case presentation We present the case of a healthy 8-year-old boy of German descent diagnosed with necrotic acute acalculous cholecystitis, exhibiting only mild inflammatory signs and an unspecific clinical presentation of abdominal pain. There was no evidence of viral, bacterial, or parasitic infection. According to his unclear clinical presentation with 2-day history of vomiting, we performed an explorative laparoscopy and detected a necrotic gallbladder. After laparoscopic cholecystectomy, the patient’s health status improved immediately. He was discharged from the hospital on the third day after the operation. Conclusion Unlike our patient, almost all cases of acute acalculous cholecystitis originate from viral or bacterial infections, with clinical evidence of gallbladder inflammation shown on diagnostic imaging. An exploration of the abdominal cavity during a laparoscopic procedure was vital to our patient’s mortality and could be for others as well.